Kinetic Study of Pb(II) Adsorption on Food-grade κ-Carrageenan Beads - Felice Pricilla Hilmawan; Khalisha Rhea Amalia; Muhammad Iqbal; Syifabudi Chairurrizky; Untung Triadhi (Faculty of Engineering, Universitas Serambi Mekkah, 2024)
Heavy metal contamination in open waters is one of the most urgent environmental problems that needs to be addressed. Pb(II) ion is a toxic heavy metal ion and is often found contaminating nature. Adsorption is one of the methods that is widely used to overcome heavy metal ion pollution such as Pb(II). One source of material that is low-cost, environmentally friendly, and readily available for use as an adsorbent is carrageenan. Carrageenan is an anionic polysaccharide and is a biopolymer that is widely found in the red algae Rhodophyceae. In this research, the adsorbent of κ-carrageenan beads made from food-grade κ-carrageenan cross-linked with K+ions was successfully made for the adsorption of Pb(II) ions which was confirmed using FTIR. The adsorbent swelling degree was 25.57% in aqua dm and 83.44% in 100 ppm Pb(II) solution. The results of the adsorption kinetics study show that adsorption follows a pseudo-second order kinetic model with a rate constant of 0.03399 g mg−1 min−1 and an adsorption capacity of 5.48 mg/g